Technologies in Decline: Socio-Technical Approaches to Discontinuation and Destabilisation - Zahar Koretsky; Peter Stegmaier; Bruno Turnheim; Harro van Lente (Routledge, 2023)
The central questions of this book are how technologies decline, how societies deal with technologies in decline, and how governance may be explicitly oriented towards parting with 'undesirable' technology. Surprisingly, these questions are fairly novel. Thus far, the dominant interest in historical, economic, sociological and political studies of technology has been to understand how novelty emerges, how innovation can open up new opportunities and how such processes may be supported. This innovation bias reflects how in the last centuries modern societies have embraced technology as a vehicle of progress. It is timely, however, to broaden the social study of technology and society: next to considering the rise of technologies, their fall should be addressed, too. Dealing with technologies in decline is an important challenge or our times, as socio-technical systems are increasingly part of the problems of climate change, biodiversity loss, social inequalities and geo-political tensions. This volume presents empirical studies of technologies in decline, as well as conceptual clarifications and theoretical deepening. Technologies in Decline presents an emerging research agenda for the study of technological decline, emphasising the need for a plurality of perspectives. Given that destabilisation and discontinuation are seen as a way to accelerate sustainability transitions, this book will be of interest to academics, students and policy makers researching and working in the areas of sustainability science and policy, economic geography, innovation studies, and science and technology studies.
Keywords: 330; Development economics and emerging economies; Applied ecology; Environmental science; engineering and technology